IMPLEMENTASI STRATEGI PENINGKATAN LOYALITAS PELANGGAN MELALUI CORPORATE BRAND EQUITY, PRODUCT ATRIBUTE DAN SERVICE QUALITY STUDI KASUS PADA PERUSAHAAN DISTRIBUSI BAHAN BAKU BAKERY DAN PASTRY UNTUK WILAYAH PEMASARAN JAKARTA DAN BANDUNG - Anik Tri Suwarni; Ardianto Nugroho; Nurlina Rahman (Universitas Mercu Buana, 2015)
Abstract: Research on the branch of marketing strategy aims to obtain a picture of the perceptions of producers Bakery and Pastry in Jakarta and Bandung related efforts to increase their loyalty in rebuying raw materials due to the strengthening of Corporate Brand Equity, which influenced Product attributes and Service Quality. Population unit is the manufacturer Bakery and Pastry in Jakarta and Bandung, which has become a customer minimal 1 year, totaling 468 employers. Research is using SEM analysis tools, with 150 respondents drawn proportionally in the two study areas. Research results inform that: (1)Product attributes (ProdAt) does not directly influence the Corporate Brand Equity (CBE); (2) Service Quality (ServQ) directly influence the CBE; (3) CBE affect the Customers Loyalty (CustLoy); (4) ProdAt directly influence CustLoy; and (5) ServQ directly influence CustLoy. Recommended for: 1) Increase the required CustLoy CBE intervening variables. 2) Maintain and develop the dimensions of each variable, except the dimensions of the variable ServQ distribution services must be improved in order to simultaneously improveCustLoy through CBE.Keywords: Marketing Strategy, Customer Loyalty, Corporate Brand Equity, Product Attribute, Service Quality.